(untitled) (Medicine Today, 2013)
Lead poisoning is one of the burning issues in Bangladesh. This study assessed the relation of blood lead level with IQ and peripheral nerve function in environmental lead exposed primary school children in Dhaka. Blood lead level (BLL) was measured in 84 primary school children in an urban industrial area of Dhaka. IQ was measured with Wechsler Intelligence Scales- Revised for children. Electrophysiological evaluation was done in 31 children. Verbal, Performance and Full scale IQ had a negative correlation with blood lead level (p<0.001). Decrement in Verbal, Performance and Full scale IQ associated with 1 microgram per deciliter increase in blood lead level were 0.99, 0.86 and 0.95 respectively (p<0.001). None had clinical features of neuropathy. Statistical analysis also did not show any significant difference in NCS between children with normal and elevated BLL (p value >0.05). It was found that IQ of children decreased in a linear trend with increasing blood lead level. This study did not find any clinical or electrophysiological evidence of peripheral nerve dysfunction in the environmental lead exposed children. DOI: http://dx.doi.org/10.3329/medtoday.v25i1.15899 Medicine Today 2013 Vol.25(1): 1-5